Subclinical cardiovascular risk signs in adults with juvenile idiopathic arthritis in sustained remission - Inmaculada Concepción Aranda-Valera; Iván Arias de la Rosa; Rosa Roldán-Molina; María del Carmen Ábalos-Aguilera; Carmen Torres-Granados; Alejandra Patiño-Trives; María Luque-Tevar; Alejandro Ibáñez-Costa; Rocío Guzmán-Ruiz; María del Mar Malagón; Alejandro Escudero-Contreras; Chary López-Pedrera; et al. (BMC, 2020)
Abstract Background Juvenile Idiopathic Arthritis (JIA) is one of the most common chronic diseases of childhood that often persists into adulthood and can result in significant long-term morbidity. As a long lasting chronic inflammatory disease, concern has been raised regarding the risk of premature development of cardiovascular disease (CVD) in JIA. This study aims to determine whether adults with JIA in clinical remission display clinical and subclinical signs of CVD risk: inflammatory mediators, adipokines, endothelial dysfunction and oxidative stress markers. Methods This is a cross-sectional study including 25 patients diagnosed with JIA according to the International League of Associations for Rheumatology criteria (ILAR 2001) and 25 age- and sex-matched controls. Remission was determined by JADAS10 < 1 and according to Wallace criteria. The presence of traditional CVD risk factors was analyzed. An extensive clinical analysis including body mass index (BMI), lipid profile, homeostatic model assessment - insulin resistance (HOMA-IR) and arterial blood pressure was performed. Intima media thickness of the common carotid artery (CIMT) was measured as a marker of subclinical atherosclerosis. Several proinflammatory cytokines, molecules involved in the endothelial dysfunction, oxidative stress and adipokines were quantified on serum by ELISA and on peripheral blood mononuclear cells (PBMCs) by RT-PCR. In vitro studies were carried out in healthy PBMCs, adipocytes and endothelial cells which were treated with serum from JIA patients under sustained remission. Results Mean duration of the disease was 13.47 ± 5.47 years. Mean age was 25.11 ± 7.21. Time in remission was 3.52 ± 3.33 years. Patients were in remission with no treatment (40%) and with treatments (60%). CVD risk factors and CIMT were similar in JIA patients and controls. However, cholesterol levels were significantly elevated in JIA patients. Levels of adipocytokines, oxidative stress and endothelial activation markers were elevated in serum and PBMCs from JIA patients. Serum of those JIA patients induced the activation of adipocytes, endothelial cells and healthy PBMCs. Conclusions JIA adult patients in remission have subclinical signs of inflammation and CVD risk, showed by an increase in the levels of inflammatory cytokines, endothelial activation and oxidative stress markers and adipokines, molecules closely involved in the alteration of the vascular system.